Neuroinflammation in Schizophrenia: An Overview of Evidence and Implications for Pathophysiology - Evgeny Ermakov; Irina Mednova; Anastasiia Boiko; Svetlana Ivanova (Journal of Integrative Neuroscience)
Neuroinflammation, meaning an inflammatory process primarily occurring within the central nervous system (CNS), is thought to be associated with the pathogenesis of psychiatric disorders including schizophrenia (SC), although existing evidence is sometimes contradictory. This review critically summarizes the existing data on neuroinflammation and possible neuroinflammatory mechanisms in the pathogenesis of SC. Despite heterogeneity and inconsistency, the existing evidence indicates dysregulation of inflammatory genes and infiltration of the CNS parenchyma by immune cells, disturbances in the blood–cerebrospinal fluid barrier and blood–brain barrier, and activation of microglia and astroglia. Widely documented increases in levels of peripheral inflammatory biomarkers also reflect activation of inflammatory processes in the CNS. Nevertheless, patients differ in the degree of activation of neuroinflammatory processes, indicating the existence of immunophenotypes of SC with and without neuroinflammation. Neuroinflammation may be associated with dysregulation of synaptic pruning, impaired neuroplasticity, glymphatic-clearance dysfunction, and white-matter pathology, all of which may ultimately lead to functional brain dysconnectivity and disease manifestation. Dysregulation of the hypothalamic–pituitary–adrenal axis and gut–brain axis and disturbances in the kynurenine pathway are the main molecular mechanisms linking peripheral and central inflammation. However, neuroinflammation may not only be associated with negative consequences but also indicate activation of adaptive and reparative processes. Thus, neuroinflammation may be entwined in the pathogenetic mechanisms of SC; therefore, anti-inflammatory therapeutic strategies may improve patient care.